True Stories : A Show Related to an Era - The Eighties - Pakesch, Peter; Hetzler, Max; Holzwarth, Hans Werner; Eitel, Lutz; Schürmann, Wilhelm (Berlin : Galerie Max Hetzler : Holzwarth Publications, 2019)
Bałka, Mirosław ; Brandl, Herbert ; Büttner, Werner ; Clegg & Guttmann ; Esterhazy, Mathis ; Förg, Günther ; Genzken, Isa ; Gober, Robert ; Gonzalez-Torres, Felix & Wool, Christopher ; Herold, Georg ; Hütte, Axel ; Iglesias, Cristina ; Kelley, Mike ; Kippenberger, Martin ; Koons, Jeff ; Larner, Liz ; Leonard, Zoe ; Mahn, Inge ; Meuser ; Mucha, Reinhard ; Noland, Cady ; Oehlen, Albert ; Oehlen, Markus ; Prince, Richard ; Sattmann, Didi ; Schnabel, Julian ; Schürmann, Wilhelm ; Sherman, Cindy ; Simoni, Mariella ; Struth, Thomas ; Trockel, Rosemarie ; West, Franz ; Winters, Terry ; Zobernig, Heimo
True Stories: A Show Related to an Era - The Eighties. Part I, Galerie Max Hetzler, Berlin, 14 September to 27 October 2018 ; Galerie Max Hetzler, London, 29 September to 19 October 2018 - True Stories. Part II, Galerie Max Hetzler, Berlin, 9 November to 22 December 2018
boek